Formulation of Simpangdago.com Website Development Plan Using Multidimensional Approach for Web Evaluation - Tanjung, Farid Aulia; Dhewanto, Wawan (The Indonesian Journal of Business Administration, 2013)
The rapid growth of the Internet in Indonesia is creating rapid growth in e-commerce industry. In 2011, internet users are 68,5 million or around 25% of Indonesian population. In general, the average transaction per online users in Indonesia has reached US 68,3/year or US 5,69/month. Based on average transaction per user, Indonesian e-commerce industry predicted to continue to grow in line with growth of Indonesian internet users.Â Simpangdago.com created to be a part of rapid growth in Indonesia e-commerce factor. Using corporate strategy analysis, it can be identified that they need product development as corporate strategy. Development strategy is formulated using multidimensional approach for web evaluation based on web user satisfaction. Method that implemented in web user satisfaction is questionnaire survey. Target respondent, which is majority young people, is filled some question which constructed to identify satisfaction level. Result from survey is analyzed using multidimensional approach that consists of usability testing and user feedback. A main goal from analysis is identify innovation areas of opportunity to increase user satisfaction and create competitive values of company. Final result of this study is set of recommendation that should be implemented by Simpangdago.com to improve company performance. Recommendation consists of web concept formulation and web features formulation that needed to modify in web system.Â Keywords: corporate strategy, web user satisfaction, muldimensional approach, usability testing, user feedback.